PERTANGGUNGJAWABAN ORGAN YAYASAN ATAS PAILITNYA YAYASAN MENURUT UNDANG-UNDANG NOMOR 16 TAHUN 2001 Jo UNDANG-UNDANG NOMOR 28 TAHUN 2004 TENTANG YAYASAN - NUR HIDAYAH; RAMLI SIREGAR; WINDHA WINDHA (Universitas Sumatera Utara, 2013)
Foundation is a legal entity generally in education, health, the field of religion, culture, social areas,and humanitarian who has no members. Foundation runs its activities througt organ foundation, namely builder, administrators, and supervisors. Organ foundation in managing foundations can lead to a foundation for bankruptcy is not always caused by negligence organ foundation in managing the foundation. The issue in this skripsi is how legal regulation on the management of the foundation according to law number 16 year 2001 Jo. Law number 28 year 2004 on the foundation, how bankruptcy foundation, as well as how accountability organ foundation bankruptcy foundations. The research method used type of normative legal research. Source of data used are secondary data, which consists of primary legal materials, secaondary, and tertiary. Data was collected by the engineering literature study and analysis of data using qualitative and inductive approach dedukatif. Setting the foundation by law include the eatablishment of the foundation that requires the establishment of foundations in the notarial deed, also be set on a foundation consisting of organ builder, administrators, and supervisors. A foundation can suffer due to bankruptcy because the foundation has two or more creditors and not pay in full at least one debt that has matured and can be billed, declared bankruptcy by court. Organ responsible for bankruptcy foundation is provided for in law foundation that is if bankruptcy occurred because of errors or omissions in the wealth management and supervisory foundation is not enough to cover the losses caused by bankruptcy. Kata kunci : Tanggung Jawab, Organ, Yayasan,Kepailitan